A review on microbial identification system-Gen III Micro Log, a unique metabolic finger-print for identification of phenol degrading bacteria. - K. PUNNY; D. DIVYA TEJA; V. SRIDEVI (International Journal of Pharma and Bio Sciences, 2018)
The Climate and surroundings of industrial areas are mostly exposed to hazardous impacts and anthropogenic contamination generated from road traffic, fossil fuel combustion, ore mining industry and pharmaceuticals. The deviations in parameters of isolated strains are attributed to adapt to the polluted environment conditions. The biodegradation potential of isolated bacteria mainly depends on the function and diversity of the microbial ecosystem. It is achievable and it is used to detect different as well as identical characteristics of specific bacterial strains. Using a modern system of BIOLOG MicroStation, new strains were isolated and compared for biochemical identification results. Basic characteristics, their phenotypic diversity not only on the level of the genus but also on the level of the individual species. The paper offers an overview of the significance of phenotypic characterization for identification of microorganisms and their correct taxonomic classification. The Biologmicrotitre plate assay, which is based on tetrazolium dye reduction as an indicator of sole-carbon-source utilization, has been evaluated as a rapid method to investigate the biodegradation of five classes of anionic surfactant by pure and mixed cultures of bacteria. The assay gave reproducible results over a fourfold range of inoculum optical density, and the surfactant concentration was selected to provide a compromise between the length of the lag period prior to colour production and the maximum colour produced. In addition, an important benefit of the methodology is that it can be used for direct analysis of the biodegradation potential of whole bacterial communities without having to make an artificial selection during laboratory growth.